2014
DOI: 10.1371/journal.ppat.1004202
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Detection of Variant CJD and BSE Prions in Blood

Abstract: The emergence of variant Creutzfeldt Jakob Disease (vCJD) is considered a likely consequence of human dietary exposure to Bovine Spongiform Encephalopathy (BSE) agent. More recently, secondary vCJD cases were identified in patients transfused with blood products prepared from apparently healthy donors who later went on to develop the disease. As there is no validated assay for detection of vCJD/BSE infected individuals the prevalence of the disease in the population remains uncertain. In that context, the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 66 publications
2
103
1
Order By: Relevance
“…It also allowed detection of PrP TSE in whole blood collected from CD1 mice that were experimentally infected with the Rocky Mountain Laboratory (RML) prion strain of scrapie, and in whole blood from uninfected CD1 mice that was exogenously spiked with RMLinfected brain homogenate (Tattum et al, 2010a). Furthermore, very recently, PMCA was also used to detect PrP TSE in the white blood cells and buffy coat from BSE-infected sheep and vCJD-infected primates (cynomolgus monkey) during the preclinical and clinical stages of the disease, and from vCJD-affected patients (Lacroux et al, 2014).…”
Section: Amplification-based Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…It also allowed detection of PrP TSE in whole blood collected from CD1 mice that were experimentally infected with the Rocky Mountain Laboratory (RML) prion strain of scrapie, and in whole blood from uninfected CD1 mice that was exogenously spiked with RMLinfected brain homogenate (Tattum et al, 2010a). Furthermore, very recently, PMCA was also used to detect PrP TSE in the white blood cells and buffy coat from BSE-infected sheep and vCJD-infected primates (cynomolgus monkey) during the preclinical and clinical stages of the disease, and from vCJD-affected patients (Lacroux et al, 2014).…”
Section: Amplification-based Approachesmentioning
confidence: 99%
“…Some of the assays reviewed here, particularly the solidstate matrix assays (Lourenco et al, 2006;Edgeworth et al, 2011;Lacroux et al, 2014), demonstrated that it is possible to detect PrP TSE in the blood of symptomatic vCJD patients. This is a marked advance in the diagnosis of prion diseases, indicating that a blood test is possible, although not yet suitable, for routine use.…”
Section: -Test)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the occurrence of vCJD cases caused by administration of prion-infected human blood has highlighted the realistic opportunity for the development of a blood-based diagnostic test for this condition. Recent developments have shown promise with the detection of vCJD-positive blood samples from clinical vCJD cases by immuno-biochemical selection of disease-associated PrP, without the use of PK [42,43], and by detection of PK-resistant PrPSc following PMCA [44]. Since transmissibility is a defining hallmark of prion diseases, it will be important to develop a reasonably rapid and versatile confirmatory prion infectivity bioassay to supplement these biochemical-based prion diagnostic assays.…”
Section: Discussionmentioning
confidence: 99%